Identification And Characterization Of Micrococcus Flavus By 16s Rrna Sequencing (Journal of Plant Disease Sciences, 2019)
Micrococcus flavus isolated from rhizosphere samples of pomegranate was subjected to molecular characterization by 16S rRNA sequencing. Molecular phylogeny of bacteria was determined by amplifying genomic 16S rRNA region. Two primers specific to 16S rRNA region used in this study were 519F and 1385R in order to amplify approximately 850bp sequence of bacterial 16srRNA gene. DNA Extraction was carried out using HiPurA Bacterial Genomic DNA Purification Kit. The DNA isolated from bacteria was subjected to polymerase chain reaction (PCR) amplification using Biometra thermal cycler. For sequencing of PCR product 519F- 5’CAGCAGCCGCGGTAATAC3’ sequencing primer was used, whereas, bioinformatics analysis was done using online BLASTn (nucleotide Basic Local Alignment Search Tool) facility of National Center for Biotechnology Information (NCBI). The BLAST results were used to find out evolutionary relationship of bacteria. Altogether twenty sequences, including sample were used to generate phylogenetic tree. The tree was constructed by using MEGA 5 software. The result revealed that the isolate code PRM-16 showed 98 per cent homology for Micrococcus flavus.
Keywords: Micrococcus flavus; Rhizosphere; 16S rRNA sequencing; pomegranate